NEW SILK ROAD DIPLOMACY: INDIA’S CHALLENGES AND RESPONSES - GAUR, Punit; ZHOLDASBEKOVA, Akbota (CENTRAL ASIA AND THE CAUCASUS, 2019)
The historical significance of the Silk Road as a network of several interlinked trade routes connecting Eastern Europe and Africa to South and East Asia, with intersections in the present-day Eurasia or Central Asia, is well established. For the last couple of decades (post-U.S.S.R. disintegration period), voices have been heard from all over the world calling for a revival of the ancient Silk Road with the aim of enhanced overland commercial cohesiveness in the region connected/covered by it. However, the continuous war in Afghanistan over the course of the last three decades and uncertainty in Central Asia have continuously rendered the idea of revival unviable, up until the present time.Efforts aimed at the revival of the Silk Road seem to be gaining renewed momentum lately. It is important to note that the present-day major international powers have their own, distinct concepts of the revival of the Silk Road that seem to be moving ahead at varying paces, operating parallel to each other, if not exactly coinciding.With all the above inferences, India is still in the process of expanding the association, which would eventually lead to close engagement with major powers. In the rapidly changing geopolitical scenario, some of the most important challenges for India are the adverse economic effects of the world economy and energy security, along with Geo cultural relevance in the context of the Islamic State and fundamentalism. In this context, this paper aims to elaborate on India’s challenges and responses for a new Silk Road diplomacy.